1988
DOI: 10.1104/pp.86.4.1120
|View full text |Cite
|
Sign up to set email alerts
|

Light-Harvesting Chlorophyll a/b Protein

Abstract: The apoprotein of the light-harvesting chlorophyll alb protein (LHCP) is a major integral thylakoid membrane protein that is normally complexed with chlorophyll and xanthophylls and serves as the antenna complex of photosystem IL LHCP is encoded in the nucleus and synthesized in the cytosol as a higher molecular weight precursor that is subsequently imported into chloroplasts and assembled into thylakoids. In a previous study it was established that the LHCP precursor can integrate into isolated thylakoid memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 14 publications
2
44
0
Order By: Relevance
“…What could be the cause for the differential processing? Differential processing of pre-LHC proteins has already been reported in in vitro studies for wheat, pea, tobacco, tomato, and corn (5,6,8,27,35). A secondary processing site in the wheat sequence is believed to be within the mature protein (7) and is, interestingly, beyond Thr3, which has been found to be phosphorylated in thylakoid membranes from spinach and Arabidopsis (31,45).…”
Section: Discussionmentioning
confidence: 99%
“…What could be the cause for the differential processing? Differential processing of pre-LHC proteins has already been reported in in vitro studies for wheat, pea, tobacco, tomato, and corn (5,6,8,27,35). A secondary processing site in the wheat sequence is believed to be within the mature protein (7) and is, interestingly, beyond Thr3, which has been found to be phosphorylated in thylakoid membranes from spinach and Arabidopsis (31,45).…”
Section: Discussionmentioning
confidence: 99%
“…This is not unexpected since LHCP and pLHCP can both be reconstituted with pigments in vitro to form complexes of very similar structure and stability (Paulsen and Hobe, 1992). Moreover, it has been shown that both LHCP and pLHCP can be assembled into LHCII in vitro (Chitnis et al, 1988;Cline 1988). In Fig.…”
Section: Lhcp In Pigmented Complexes Has a Higher Content Of A-helix mentioning
confidence: 97%
“…1C), which is found solely in the chloroplasts (15). Although the precursor associated with the mitochondria (lane 2), it was completely digested by Proteinase K (lane 3), suggesting that its association was through nonspecific interactions with the outer membrane.…”
Section: Import Of Precursors Into Isolated Pea Mitochondria-mentioning
confidence: 99%